Development and Testing of a Small-Size Olfactometer for the Perception of Food and Beverages in Humans - Risso, Paola; Covarrubias Rodriguez, Mario; Bordegoni, Monica; Gallace, Alberto (Frontiers in Digital Humanities, 2018)
Studies of olfactory perception and about the way humans interact with, and perceive food and beverages require appropriate olfactory devices. Moreover, small size, and portable interfaces are needed within the context of Human Computer Interaction (HCI), to enrich and complete the design of different mediated experiences. In this paper, the authors tested a new portable olfactory device for the orthonasal administration of smells. The aim was at verifying if the experience generated by the odors delivered through such device can affect people’s perception of taste. Once established that people could perceive odors using the olfactory device, a group of participants was asked to taste two different types of food (Experiment 1) and three types of beverages (Experiment 2) and to evaluate them on a number of perceptual-dimensions (such as pleasantness, freshness, sweetness, saltiness and bitterness). The participants could taste the food and the beverage without the presence of additional olfactory stimuli or under conditions where olfactory stimuli (smell of chocolate or citrus) were also presented by means of the device. The results showed that the participants’ evaluation of food and beverages were significantly modulated by the concurrently presented odors. The experimental results suggest that: 1) the device is effective in controlling the delivery of odours to human participants without the complexity of management that often affect larger odours delivery systems; 2) odors administered by means of such device can have an effects on food and beverage perception, without the need to change their chemical properties.